Estimation of Levels of Interleukin-1 beta and Interleukin-10 in Sera of some Iraqi Patients with Chronic Rheumatoid Arthritis - Subhi, Israa M.; Zgair, Ayaid K. (Iraqi Journal of Science, 2018)
Serum samples were obtained from patients suffering from chronic Rheumatoid Arthritis (RA) disease. They were divided into three groups; 20 patients with RA taking biological treatment Etanercept (Enbrel), 20 patients with RA not taking biological treatment (disease modifying anti-rheumatic drug) and 10 people as healthy control group. The ages of these patients and control group were between 46-50 years old; one male and 19 female in each group. The samples were used for measuring the levels of Interleukin (IL)-1 Beta and Interleukin-10 using the Enzyme Linked Immunosorbent Assay technique. Both interleukins were at their highest levels in the group of RA patients treated with biological treatment followed by the RA patients group that were not treated with biological treatment and the lowest levels were in the healthy control group.